An approach for voltage drop improvement in 22 kV PEA distribution system based on high voltage capacitor placement - Surakit Thongsuk; Atthapol Ngaopitakkul; Wikorn Kotesakha; Monthon Leelajindakrairerk; Chaichan Pothisarn; Suntiti Yoomak (Energy Reports, 2023)
The distribution system has been constantly expanded with rising load demand due to population and economic growth. The result is a distribution line facing a voltage drop issue voltage drop, which results from increasing interconnected load and the distance from the substation. To mitigate this issue, this paper proposed an approach to improve the voltage level on the distribution line using a high-voltage capacitor bank. The system under study is modeled after the Provincial Electricity Authority (PEA) 22-kV distribution line. The placement of the high voltage capacitor bank will be based on the 2/3 rule technique. The PSCAD/EMTDC has been used to simulate the characteristics of the case study distribution system and evaluate the performance of the proposed technique in comparison with the PEA voltage regulation standard. The result has demonstrated the ability to use the proposed high voltage capacitor bank placement technique to improve voltage levels in the distribution system.
Keywords: Optimal Power Flow Distribution; Smart Grid Energy Management; Power System Optimization and Stability